Telaah Kurikulum dalam Mata Pelajaran Al-Qur’an Hadist di Madrasah Ibtidaiyah - Purniadi Putra; Idawati Idawati (JIP Jurnal Ilmiah PGMI, 2017)
The curriculum of Al-Qur'an Hadith in MI developed is expected to ensure the growth of faith and devotion towards Allah SWT, improvement of life skills, ability to work and be scientific while ensuring the development of a strong personality and berakhlaq noble. Method: This research using literature approach (libarary research). The subject of this research is the curriculum at the grade of 1,2 and 3 in Madrasah Ibtidaiyah. Results: For the basic competencies presented in classes 1, 2 and 3 can not be implemented maximally because the basic competence mentioned learners are required to pronounce and memorize short verses correctly and eloquently.